Financial information security using hybrid encryption technique on multi-cloud architecture - Mustafa Noori Rashid; Leith Hamid Abed; Waleed Kareem Awad (Bulletin of Electrical Engineering and Informatics, 2022)
One of the most severe issues in the cloud is security. In comparison to financial data, so it is extremely sensitive and must be safeguarded against unwanted access. We have developed a proposed system based on three different keys. We divided the data into insensitive, sensitive, and highly sensitive data. The data will be saved on a separate cloud server. The proposed system used different keys for encryption and decryption purposes. The elliptic curve cryptography (ECC) based distributed cloud-based secure data storage (DDSPE) approach was proposed to provide secure large data based data protection across the different clouds. With DDSPE technology, the ECC scheme has been used for encryption and decryption purposes. The cloud is used for simulation. The results of the tests reveal that the suggested DDSPE system is safe and saves time regarding data retention and retrieval. To analyze performance, we compared the DDSPE method with advance encryption standard (AES), blowfish, rivest shamir adleman (RSA), security-aware efficient distributed storage (SA-EDS), and attribute based encryption (ABE) based secure distributed storage (ASDSS). In terms of information retention and recovery, our methodology is quite effective because it requires less amount of time as compared to other strategies.